2020
DOI: 10.3831/kpi.2020.23.001
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Addiction: Neurobiology and Mechanism

Abstract: Nicotine, primary component of tobaco produces craving and withdrawal effect both in humans and animals. Nicotine shows a close resemblance to other addictive drugs in molecular, neuroanatomical and pharmacological, particularly the drugs which enhances the cognitive functions. Nicotine mainly shows its action through specific nicotinic acetylcholine receptors located in brain. It stimulates presynaptic acetylcholine receptors thereby enhancing Ach release and metabolism. Dopaminergic system is also stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…One of the previous studies investigated the mRNA expression of the interleukins IL-1, IL-6, IL-17, miR-9, and miR-122 as potential useful indicators for non-small cell lung cancer (NSCLC). It was observed that the expression of selected interleukins in noncancerous tissues was significantly higher than that in tumor tissues, and patients with a history of 40 pack-years (PY) (2,197, IQR: 0.821-4.415) and who were over 40 years old (0.461, IQR: 0.372-0.741; p = 0.037) had significantly greater levels of IL-6 in their tumor tissues. The up-regulation of IL-1 and IL-6 in tumors and surrounding tissues suggests that firing cycles have a role in NSCLC, and smoking can affect inflammation during tumorigenesis, which is manifested by an increase in IL-6 in patients' tumor tests [18].…”
Section: Fagerstrom Nicotine Dependence Test and Lipopolysaccharide Level Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the previous studies investigated the mRNA expression of the interleukins IL-1, IL-6, IL-17, miR-9, and miR-122 as potential useful indicators for non-small cell lung cancer (NSCLC). It was observed that the expression of selected interleukins in noncancerous tissues was significantly higher than that in tumor tissues, and patients with a history of 40 pack-years (PY) (2,197, IQR: 0.821-4.415) and who were over 40 years old (0.461, IQR: 0.372-0.741; p = 0.037) had significantly greater levels of IL-6 in their tumor tissues. The up-regulation of IL-1 and IL-6 in tumors and surrounding tissues suggests that firing cycles have a role in NSCLC, and smoking can affect inflammation during tumorigenesis, which is manifested by an increase in IL-6 in patients' tumor tests [18].…”
Section: Fagerstrom Nicotine Dependence Test and Lipopolysaccharide Level Correlationmentioning
confidence: 99%
“…Although nicotine is the most addictive cigarette smoking element, several synthetic chemicals also contribute to the addictive concept of cigarette smoking, either directly or indirectly. Nicotine, carbon monoxide, receptive oxidant substances (ROS), and acrolein are among the more significant tobacco smoke poisons with immunomodulatory potential, albeit a lot more may exist [1], [2]. Nicotine, an essential part of Tobacco, produces wanting and withdrawal impact both in people and creatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for about 931 million US dollars per year, an indication that the implementation and effective operationalization of the World Health Organization Framework Convention on Tobacco Control (FCTC) of 2005 and the National Tobacco Act of 2015 is still a mirage in the country (WHO 2015 ; Ayodapo and Ibisola 2021 ). It is a psychoactive plant readily available in every corner of the earth (Tiwari et al 2020 ).
Fig.
…”
Section: Psychoactive Plantsmentioning
confidence: 99%
“…Another alkaloid involved in mesolimbic dopamine system activation during N. tabacum exposure is cotinine. Cotinine increases dopamine release through a Ca + –dependent pathway (Tiwari et al 2020 ). Aside from the mesolimbic dopamine system, the serotonergic transmission system is also altered during N. tabacum exposure.…”
Section: Psychoactive Plantsmentioning
confidence: 99%